ECOFEMINISM IN THE DIGITAL AGE: CHALLENGES, MOVEMENTS, AND INNOVATIONS - Yadav, Rekha; Kumar, Suresh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper explores the intersection of ecofeminism and digital technology in the 21st century, examining how the digital age has transformed ecofeminist discourse, activism, and literary expression. Through an analysis of contemporary literature, digital platforms, and online movements, this study investigates the challenges faced by ecofeminism in the digital era, the innovative ways in which ecofeminist ideas are disseminated and enacted online, and the emergence of new forms of ecofeminist expression in digital literature. The paper argues that while digital technologies present new challenges for ecofeminist thought, they also offer unprecedented opportunities for global collaboration, consciousness-raising, and creative expression. By examining case studies of digital ecofeminist movements and analyzing works of electronic literature that engage with ecofeminist themes, this research contributes to our understanding of how ecofeminism is evolving in response to the digital revolution.